If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 110 + 6x = 8x + 114 Reorder the terms: 110 + 6x = 114 + 8x Solving 110 + 6x = 114 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 110 + 6x + -8x = 114 + 8x + -8x Combine like terms: 6x + -8x = -2x 110 + -2x = 114 + 8x + -8x Combine like terms: 8x + -8x = 0 110 + -2x = 114 + 0 110 + -2x = 114 Add '-110' to each side of the equation. 110 + -110 + -2x = 114 + -110 Combine like terms: 110 + -110 = 0 0 + -2x = 114 + -110 -2x = 114 + -110 Combine like terms: 114 + -110 = 4 -2x = 4 Divide each side by '-2'. x = -2 Simplifying x = -2
| y/4= | | 2cos3pi/8*cospi/8 | | 3v-9=33 | | 18*3.14+6*3.14x=420 | | 2cos3pi/8 | | 1.67/0.75 | | F(x)=11x^2+13x | | 2tanx+9=7 | | -5/3X-1/4=-1/6X-1/8 | | 5n^2+8n-10=0 | | 82-62=10x-15x | | (n/4)-5=8 | | 5c-13=8-2c | | -4(0)+2y=7 | | Sec^2x=4tan^2x | | -4x+2(0)=7 | | 4m+3=16 | | 2(-2)+3y=-4 | | 2x+3(0)=-4 | | 3(y-6)-2(5+3y)=5 | | 2(y+6)+1=3y+12-y | | X*4+6=20 | | 8(-1.25)-3y=-10 | | 2x^2-5x=-2is | | 8x-3(0)=-10 | | 3/1*8/9*4/11 | | 2x^2+mx=-2 | | 1/5*3/4*5/7 | | 2(y+6)=3y+12-y | | 5-3(x+2)=2x-7 | | -9+15=3x-18 | | 4x+y=3x+12 |